How shall we examine and learn about public-private partnerships (PPPs) in the health sector? Realist evaluation of PPPs in Hong Kong. (December 2015) - Wong, Eliza L.Y.; Yeoh, Eng-kiong; Chau, Patsy Y.K.; Yam, Carrie H.K.; Cheung, Annie W.L.; Fung, Hong
Abstract: The World Health Organization advocates the goal of universal coverage of health systems to ensure that everyone can avail the services they need and are protected from the associated financial risks. Governments are increasingly engaging and interacting with the private sector in initiatives collectively referred to as public-private partnerships (PPPs) to enhance the capacity of health systems to meet this objective. Understanding the values that motivate partners and demonstrating commitment for building relationships were found to be key lessons in building effective PPPs; however there, remain many research gaps. This study focusses on the practice of PPPs at the inter-organisational (meso) level and interpersonal (micro) level in Hong Kong Special Administrative Region (HKSAR). The influence of the structural components of different PPPs on stakeholder interpretation and actions, as well as the eventual outcomes of the PPPs, is examined, in terms of a realist evaluation, which applies a context–mechanism–outcome configuration as the research methodology. Seven key factors initiating commitment in a partnership, critical for sustainable PPPs, were identified as follows: (1) building of trust; (2) clearly defined objectives and roles; (3) time commitment; (4) transparency and candid information, particularly in relation to risk and benefit; (5) contract flexibility; (6) technical assistance or financial incentive behind procedural arrangements; and (7) the awareness and acceptability of structural changes related to responsibility and decisions (power and authority). Highlights: Definition and conceptualization of PPPs are inconsistent in different countries. Heterogeneity of PPPs in different contexts is important during evaluation. Realist evaluation was recommended methodology to better understand the impact of PPPs. 7 key factors were identified for the role of PPP in strengthening health system.